CAMPURAN INFUSA SINGKONG (Manihot esculenta), KACANG KEDELAI (Glycine max (L.) Merrill) DAN EKSTRAK RAGI SEBAGAI MEDIA ALTERNATIF PERTUMBUHAN BAKTERI Staphylococcus aureus - Martha Atik Martsiningsih; Fardhiasih Dwi Astuti; Menik Kasiyati; Suyana Suyana; Ullya Rahmawati; Muji Rahayu; Ajeng Puspa Aeni (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2024)
The composition of nutrients needed by bacteria varies greatly such as peptone, meat extract, and agar. Nutrient Agar is one of the media used as a bacterial culture that has a composition such as protein and carbohydrates in the form of meat extract and peptone that suits the needs of most bacteria. The carbohydrate content in cassava, protein in soybeans, and nitrogen sources in yeast extract can be combined into alternative media used as bacterial growth media to determine whether the alternative media combination of cassava carbohydrate source infuse, soybean infuse, and yeast extract can be used to grow Staphylococcus aureus bacteria. This research is a pure experimental study with Post Test-Only Control Design research design. The mean growth in the number of colonies of Staphylococcus aureus bacteria on alternative media was 78,25 x  CFU/ml and NA media was 94.19 x   CFU/ml with a mean difference of 15.94 x  CFU/ml or 16.92%. The mean growth diameter of the number of colonies of Staphylococcus aureus bacteria on alternative media was 2.63 x  CFU/ml and NA media was 2.66 x   CFU/ml with a mean difference of 0.03 x  CFU/ml or 1.12%. The percentage of effectiveness of Staphylococcus aureus bacterial growth is 83.07% or moderately effective and the percentage of effectiveness of Staphylococcus aureus bacterial proliferation is 98.87% or effective. Alternative media mixture of cassava infuse (Manihot esculenta crantz), soybean (Glycine max (L.) Merrill) and yeast extract can be used to grow Staphylococcus aureus bacteria.